PENGARUH BAURAN PEMASARAN DALAM BISNIS INDUSTRI BATIK TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PADA PT. BANGSAWAN INDONESIA TEKSTIL GRESIK - Ariefah Sundari; Ana Fitriyatul Bilgies; Ahmad Fathur Rozi (J-MACC, 2021)
This study aims to knowing the influence of marketing mix in Bali convection business on cunsomer satisfaction and loyalty in PT. Bangsawan Indonesia Tekstil. This study is explanatory research. Population is all all employees CSR of PT. Petro Kimia Gresik who ordered work uniforms in outlet PT. Bangsawan Tekstil Indonesia. The sampling method for this study was doing with accidental sampling technique and it got 125 respondents. Data analysis method is Structural Equation Modelling (SEM). The results of research are marketing mix which included product, price, place, and promotion have affected significantly towards customer's satisfaction. It indicated that selling product same as customer's needs and wants, the giving price is reached by consumers, location of buying product is strategic, and promotion same as consumer's hope. Marketing mix which included product, price, place, and promotion have not affected significantly towards customer's loyalty. It indicated that the selling product, the giving price, strategic location, and completed promotion could not change consumer to become loyalty at PT. Bangsawan Tekstil Indonesia. Customer's satisfaction have affected significantly towards customer's loyalty. It indicated that loyal customer is always feels satisfy with anything they received.